Fractional order plus-negative sequence decoupling control strategy for dynamic voltage restorer - WU Chaojun; WANG Zhenyue; YANG Ningning; SHAO Wenquan (电力工程技术)
In order to improve the performance of dynamic voltage restorer (DVR) in controlling asymmetrical voltage sag fault, a fractional order plus-negative sequence decoupling control strategy based on instantaneous symmetric component method is proposed and applied to three-phase four-bridge inverter DVR system. Firstly, the partial sequence decoupling mathematical model of the DVR system is obtained by using the symmetric component method. Secondly, to solve the problem that the traditional symmetric component method is not suitable for the analysis of the transient process of the system, the positive and negative zero sequence components of the instantaneous value of the asymmetric voltage and current signal are obtained by using the instantaneous symmetric component method. Then, the integer order plus-negative order decoupling control strategy is extended to fractional order, and the frequency domain method is combined with the robustness condition when the gain changes to correct the relevant parameters. Finally, the simulation results verify the feasibility of the fractional order plus-negative sequence decoupling control strategy applied to the DVR system, and the proposed strategy has better dynamic response speed and anti-interference performance than the traditional plus-negative sequence decoupling control startegy.